A physical model for long term data retention characteristics in 3D NAND flash memory. (January 2023) - Saikia, Rashmi; Mahapatra, Souvik
Highlights: Data retention characteristics analysis. Modeling of the data retention components using the Activated Barrier Double Well Thermionic Model. Extraction of the De- trapping and Lateral migration components using the model from the total ΔVt Shift. It is been shown that as temperature increases the de-trapping and LM components, both increase, also as we go higher in the states the contribution from both increases. This model can help estimate the accurate lifetime of flash cell production level. Abstract: An Activated Barrier Double Well Thermionic Emission (ABDWT) model is used to simulate long-term Data Retention (DR) in 3D NAND Flash memory cells. The contribution due to only charge De-Trapping (DT) when adjacent cells are at the same charged state and additional contribution due to charge Lateral Migration (LM) when adjacent cells are at different charged states are modeled. The Temperature (T), Program Level (PL), and Erase-Program Cycle (EPC) impacts are studied. The model simulations are verified against the experimental data from various published reports with consistent model parameters. It is shown that at higher temperatures and programming levels, the data retention increases for DT component, whereas LM component increases with the temperature and the lateral electric field.